Unraveling the seizure spectrum: differentiating between psychogenic and epileptic seizures - Jones, Kennedy, author; Jeckel, Kimberly, advisor; Maresh, Ryan, committee member (Colorado State University. Libraries, 2024)
Psychogenic non-epileptic seizures (PNES) present a unique clinical challenge, sitting at a crossroads of neurology and psychiatry. This thesis explores the potential pathophysiological and psychological framework of PNES, comparing it to epileptic seizures to outline the differences and similarities between these two distinct conditions. Through an in-depth literature review, this study will examine the physical manifestations of PNES, the diagnostic criteria, and factors contributing to these event misclassifications. Additionally, this work investigates the root causes of PNES, particularly the role of psychological stress, trauma, and mental health disorders in their onset. Key research questions focus on understanding the mechanism of PNES both physiologically and psychologically, identifying the criteria for precise diagnostic practices, and exploring the complex relationship between mental health and seizure manifestations. By analyzing current literature on both PNES and epilepsy, this research aims to clarify the boundaries between neurological and psychiatric diagnoses, while also addressing the stigma associated with PNES. The findings are expected to inform future research directions, diagnostic approaches, and treatment strategies, ultimately expanding the literature exploring the understanding and management of PNES in medical and psychological contexts.
Advisor and committee member supplied by author.
Keywords: PNES; epilepsy; psychogenic; nonepileptic; seizure; psychology; neurology